Problems of capital formation in underdeveloped countries - Nurkse, Ragnar (Oxford : Basil Blackwell, 1960)
This book, consisting largely of lectures given by Professor Nurkse in Rio de Janeiro and in Cairo, " is an attempt, on a small scale, to make use of economic theory as well as specific observation, with a view to elucidating some of the basic conditions of progress in the poorer two-thirds of the world " the author tells us. It is not (3z(Bin any sense a piece of research." It does not attempt to deal with all aspects of capital formation in underdeveloped countries. Technological development is not analysed, and although finance receives some consideration in the latter part of the book, the emphasis throughout is on the real, or nonmonetary, problems of capital accumulation in underdeveloped areas.s
Includes index.
rpm 10/11/2017
Loans
Keywords: Saving and investment; Investments, Foreign; Developing countries